Identifikasi Konseling Kelompok dalam Meningkatkan Interaksi Sosial Siswa - Misda Amallia Tuah Aji; Desi Erawati; Arini Safitri; Abdullah Sani (Institut Agama Islam Negeri Curup, 2023)
This research is motivated by the importance of social interaction in the development of students at Pondok Pesantren Hidayatul Insan. Healthy social interaction can shape character, enhance cultural diversity understanding, and provide vital adaptability skills in a social environment. However, preliminary studies have shown a lack of adequate group counseling services and insufficient student understanding of the concept of Group Guidance Counseling. The purpose of this research is to identify existing issues and provide constructive solutions to enhance the students' social interaction facilities by developing a Group Guidance Counseling program that involves collaboration with BK (Guidance and Counseling) teachers and students at Pondok Pesantren Hidayatul Insan. The research methodology employed is qualitative research with a field study approach. Data was collected through observation, interviews, and documentation. The research findings reveal that group counseling services have not been given priority in this school. BK teachers have a limited understanding of group counseling concepts, and the existing programs are still general. This situation creates a gap in students' social interaction skills. In conclusion, the role of BK teachers needs to be strengthened, and group counseling services need to be improved as an integral part of students' social interaction development. It is expected that this will contribute positively to improving students' social interactions, helping them overcome difficulties, and building healthier social relationships at Pondok Pesantren Hidayatul Insan.